Europa im Geisterkrieg Studien zu Nietzsche - Stegmaier, Werner (Open Book Publishers, 2018)
The volume unites 20 studies on Nietzsche by Werner Stegmaier, who has given strong impetus to Nietzsche's international research in the past three decades and, for eighteen years, together with Günter Abel, the Nietzsche Studies, the leading international organ of Nietzsche research. and published the monographs and texts on Nietzsche research. The studies deal with basic questions of Nietzsche's philosophy. They set (I) with its redefinition of truth and philosophy and (II) its temporalization of thinking under (III) renouncing 'reason' in the determination of man, interpret from here the (IV) anti-teachings of Nietzsche's Zarathustra, outline (V) Nietzsche's ethics for 'good Europeans' and conclude (VI) with the interpretation of Nietzsche's self-assessment as the fate of philosophy and humanity (Ecce Homo, Why I Am a Destiny 1) and an assessment of Nietzsche's future, which has started for over a century. Werner Stegmaier, born in 1946, was the founding director of the Institute of Philosophy at the University of Greifswald after the collapse of the Soviet Union and established the North and East European Forum for Philosophy, which brought the Institute of Philosophy around the Baltic Sea into new conversation with each other and there to philosophical reorientations contributed. He has worked in a variety of fields, including metaphysics and its basic concept of substance, great philosophers from antiquity to the present, the philosophical relevance of Jewish tradition, and above all to the philosophy of Nietzsche. He was always concerned with questions of First Philosophy, especially what constitutes our reality, how it is conveyed through signs and communication, how concepts exist in time and what we are dealing with in thinking. He introduced the concept of orientation as an elementary concept of philosophy and developed a comprehensive philosophy of orientation.